STABILISASI TANAH LEMPUNG EKSPANSIF GODONG-PURWODADI KM 50 MENGGUNAKAN PROSES ELEKTROKINETIK DENGAN STABILISATOR ACCU ZUUR DAN KAPUR - Wisnu Permadi; Brian Kusuma Pradipta; Siti Hardiyati; Bambang Pardoyo (Jurnal Karya Teknik Sipil, 2016)
Electrokinetic is one of the improvement methods that can be used to reducing water content of the expansive soil, by way of setting the right distance configuration of katode and anode which carrying electricity to the soil in definite distance and period. This research using accu zuur as stabilizer that helps to release water particle and flow the water from anode to katode as manifesatation of electroosmosis tendency. Results show optimum conditions from stabilization is on 20% of accu zuur, 24 hours of electrokinetics period, 25cm distance of electrode configuration and 56x of compaction.It gives results the rising of shear strength 3,557 kg/cm3 from native soil 1,799 kg/cm3. Swelling potential also decrease to 0,46% with swell pressure 0 kPa. The conclusion is accu zuur only has a function to reduce water content of the soil and lime can bind the soil particle of expansive clay soil,so the swell turn smaller than before.